2021
DOI: 10.1101/2021.09.27.461878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A serotonergic axon-cilium synapse drives nuclear signaling to maintain chromatin accessibility

Abstract: Chemical synapses between axons and dendrites mediate much of the brain's intercellular communication. Here we describe a new kind of synapse - the axo-ciliary synapse - between axons and primary cilia. By employing enhanced focused ion beam - scanning electron microscopy on samples with optimally preserved ultrastructure, we discovered synapses between the serotonergic axons arising from the brainstem, and the primary cilia of hippocampal CA1 pyramidal neurons. Functionally, these cilia are enriched in a cili… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Finally, the observation of synapses between islet cell cilia and innervating axons points to signaling functions of primary cilia beyond the local islet context. To our knowledge these kinds of connections (serotonergic cilia-axon synapses) have only been described in the brain (45). Thus, our reconstructions are the first to document this phenomenon elsewhere in the body.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Finally, the observation of synapses between islet cell cilia and innervating axons points to signaling functions of primary cilia beyond the local islet context. To our knowledge these kinds of connections (serotonergic cilia-axon synapses) have only been described in the brain (45). Thus, our reconstructions are the first to document this phenomenon elsewhere in the body.…”
Section: Discussionmentioning
confidence: 76%
“…Research has so far focused on the role of islet cell cilia in paracrine signaling between endocrine cells. Recently, however, primary cilia have been shown to form synapses with neurons in brain tissue (45). While screening the aforementioned 8 nm isotropic FIB-SEM dataset of mouse pancreas tissue (44) we found several nerve fibers contacting the islets (Fig.…”
Section: Islet Cell Primary Cilia Connect To the Pancreatic Innervationmentioning
confidence: 83%
“…In the mouse brain, ssTEM showed that ultrastructural features of the blood brain barrier, including increased pericyte-brain endothelial cell contact, are altered during aging 233 , and single axons form clustered compound multi-synaptic contacts of distinct morphologies with individual neurons, thus maximizing their influence on the postsynaptic neuron 139 . FIB-SEM has been used to demonstrate that some primary cilia form serotonergic axo-ciliary synaptic contacts in the hippocampus 234 . SBF-SEM was used to reconstruct two individual cells from a large dataset of a leech ganglion, discovering new connections 235 .…”
Section: Applicationsmentioning
confidence: 99%
“…As such, a variety of designs incorporating distinct scaffolds of GPCR molecules have been used to develop a range of serotonin sensors. For example, a cilia‐targeted serotonin sensor (GRAB‐HTR6‐PM) based on the 5‐HT 6 receptor was developed to observe serotonin release onto cilia by activation of serotonergic axons (Sheu et al, 2021). The sensor was validated in HEK cells, and HaloTag was added to improve the sensor for visualizing cilia (HTR6‐GRAB‐cilia).…”
Section: Fluorescence Imaging Methods: Genetically Encoded Fluorescen...mentioning
confidence: 99%